2010
DOI: 10.1016/j.fuel.2009.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of chars produced from pinewood pyrolysis and hydrothermal treatment

Abstract: a b s t r a c tTwo types of pinewood chars, hydrothermal char (H300) and pyrolytic char (P700) from biomass-toenergy conversion were characterized and used as adsorbent for the copper removal from aqueous solution. The result showed that the pinewood underwent a deeper carbonization during pyrolysis process and more activated sites available and stable carbon-oxygen complex existed after hydrothermal treatment. Comparing with raw pinewood, hydrothermal treatment increased 95% total oxygen-containing groups (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
142
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(163 citation statements)
references
References 29 publications
14
142
2
5
Order By: Relevance
“…3). This effect could be the result of a melting and fusion process of the lignin and other small molecule compounds, such as pectin and inorganic compounds, as described by Liu et al (2010) for pinewood biochar produced at 300 °C and 700 °C. …”
Section: Effect Of Pyrolysis Temperature On Biochar Characteristicsmentioning
confidence: 99%
“…3). This effect could be the result of a melting and fusion process of the lignin and other small molecule compounds, such as pectin and inorganic compounds, as described by Liu et al (2010) for pinewood biochar produced at 300 °C and 700 °C. …”
Section: Effect Of Pyrolysis Temperature On Biochar Characteristicsmentioning
confidence: 99%
“…Moreover, the sharp peaks centered at 1710 and 1557 cm À1 are related to carbonyl and carboxylic groups,r espectively.T he, broad peak at 895 cm À1 is characteristico ft he aromatic CÀHo ut-of-plane bending vibration. [21][22][23] Figures 3a-c show photographic images of the prepared porousc arbon as coated, thread-like, or fiber electrodes, and their excellent flexibility is highlighted. Here, the stainless-steel fiber thread is used as the currentc ollector instead of am etalcoated plastic wire [9] or metal wire, [24] because the stainlesssteel fiber thread provides more flexibility than the metal wire and better conductivity than the plastic wire.…”
mentioning
confidence: 99%
“…Material produced from gasification and/or pyrolysis has a higher ash content than biochar produced via HTC which is richer in carbon [3]. Comparison of the characteristics of biochars produced from the same pinewood source material by HTC at 300 o C or pyrolysis at 700 o C for copper adsorption from aqueous solution [5] found that HTC-biochar had more active adsorption sites and stable carbon-oxygen complexes on its surface with a 95% increase in oxygen-containing groups compared to the source material. By contrast, there was a 56% decrease in oxygen-containing groups in biochar produced by pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…carboxylic, lactone and phenolic groups) embedded within a highly porous structure. As a consequence it has a large capacity for adsorption of heavy metals, radionuclides and organic pollutants, particularly from aqueous media [5,7,8]. Many studies have reported that the time to reach equilibration for heavy metal sorption is <24 h [9][10][11].…”
Section: Introductionmentioning
confidence: 99%